Epistemological Dissonance in Islamic Family Fiqh and Digital Ethics among Vocational High School Students - Zuhairiah; Ahmad Rizky (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study addresses a critical research gap in Islamic Religious Education (IRE), focusing on the epistemological disconnect between normative Fiqh knowledge and practical digital ethics among vocational students. While digital literacy is frequently examined as a technical or civic skill, its ontological and ethical foundation within Islamic family jurisprudence (fiqh al-usrah) remains under-explored. Utilizing a qualitative case study approach, data were gathered through in-depth interviews and digital behavior observations. The findings reveal a significant